2022
DOI: 10.1021/acs.jpclett.2c00513
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Exchange and Superexchange Interactions in Dictating Electron Transfer and Reactivity in Metalloenzymes

Abstract: Electron transfer (ET) is a fundamental process in transition-metaldependent metalloenzymes. In these enzymes, the spin−spin interactions within the same metal center and/or between different metal sites can play a pivotal role in the catalytic cycle and reactivity. This Perspective highlights that the exchange and/or superexchange interactions can intrinsically modulate the inner-sphere and long-range electron transfer, thus controlling the mechanism and activity of metalloenzymes. For mixed-valence diiron ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The two electrons localized at the Mn 2+ ions are coupled by superexchange antiferromagnetically. A previous report 38 showed that exchange and superexchange interactions can dictate the catalytic mechanism and activity of metalloenzymes by influencing the electron transfer in the catalytic site. In metalloenzymes, exchange and superexchange interactions are important for the stabilization of the catalytic site.…”
Section: Resultsmentioning
confidence: 99%
“…The two electrons localized at the Mn 2+ ions are coupled by superexchange antiferromagnetically. A previous report 38 showed that exchange and superexchange interactions can dictate the catalytic mechanism and activity of metalloenzymes by influencing the electron transfer in the catalytic site. In metalloenzymes, exchange and superexchange interactions are important for the stabilization of the catalytic site.…”
Section: Resultsmentioning
confidence: 99%
“…The demonstrated ability to synthesize and control a series of complex clusters with variable stoichiometries and to probe their reactivitiesin particular water oxidation and O–O couplingunder reaction conditions that allow detailed comparisons with systematic first-principles simulations of the reaction pathways provides the impetus for further experimental and theoretical explorations using the hierarchical synthetic modeling strategy developed in this series of investigations. The uncovering of the subtle interplay between reactive pathways evolving on neighboring spin-isomeric potential-energy landscapes, belonging to ferromagnetically ordered majority spin manifolds, and of spin-gated selective processes steered by spin-conserving selection rules is expected to guide future probing of the OEC, as well as further development of catalysts for oxygen evolution reactions with an added emphasis on the role of spin, doping by magnetic atoms, magnetic ordering, synergetic spin and charge-transfer processes, and magnetic-field effects on such reactions. ,, …”
Section: Discussionmentioning
confidence: 99%
“…The uncovering of the subtle interplay between reactive pathways evolving on neighboring spin-isomeric potential-energy landscapes, belonging to ferromagnetically ordered majority spin manifolds, and of spin-gated selective processes steered by spin-conserving selection rules 11 is expected to guide future probing of the OEC, as well as further development of catalysts for oxygen evolution reactions with an added emphasis on the role of spin, doping by magnetic atoms, magnetic ordering, synergetic spin and charge-transfer processes, and magnetic-field effects on such reactions. [5][6][7][8][9][10]13,36 ■ ASSOCIATED CONTENT…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations